Advances in Clinical Child Psychology 1995
DOI: 10.1007/978-1-4757-9044-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Social Withdrawal in Childhood

Abstract: Socially withdrawn children frequently refrain from social activities in the presence of peers. The lack of social interaction in childhood may result from a variety of causes, including social fear and anxiety or a preference for solitude. From early childhood through to adolescence, socially withdrawn children are concurrently and predictively at risk for a wide range of negative adjustment outcomes, including socio-emotional difficulties (e.g., anxiety, low self-esteem, depressive symptoms, and internalizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
249
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(259 citation statements)
references
References 94 publications
9
249
0
1
Order By: Relevance
“…These findings are consistent with a previous study revealing that Chinese toddlers took significantly longer to approach attractive toys in an experimental playroom setting than their Canadian counterparts (Chen et al, 1998), indicating a high level of constraint. Past studies have revealed that a high level of behavioral control is positively valued and encouraged by parents and teachers in many East Asian countries (Rubin, Coplan, & Bowker, 2009; Chen et al, 1998), which likely contributes to South Korean infants’ high levels of Effortful Control, and may even heighten South Korean parents’ perceptions that their children are highly regulated. In addition, children from South Korea exhibit relatively low Surgency, displaying low levels of activity, impulsivity, risk-taking and desire for social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a previous study revealing that Chinese toddlers took significantly longer to approach attractive toys in an experimental playroom setting than their Canadian counterparts (Chen et al, 1998), indicating a high level of constraint. Past studies have revealed that a high level of behavioral control is positively valued and encouraged by parents and teachers in many East Asian countries (Rubin, Coplan, & Bowker, 2009; Chen et al, 1998), which likely contributes to South Korean infants’ high levels of Effortful Control, and may even heighten South Korean parents’ perceptions that their children are highly regulated. In addition, children from South Korea exhibit relatively low Surgency, displaying low levels of activity, impulsivity, risk-taking and desire for social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…While for some children the display of their reactivity to novelty is consistent across development, others may learn to cope, displaying less and less reactivity externally. In addition, toddlers with behavioral inhibition may be at risk for social withdrawal and social isolation as development continues, but not all inhibited toddlers develop these social behavior profiles (Fox et al, 2001; Rubin et al, 2009). Social reticence, a subtype of social withdrawal, has often been equated with behavioral inhibition and represents a style of social behavior where children observe peers from a distance, remaining unoccupied in either social company or non-social play (Coplan et al, 1994; Rubin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Childhood social withdrawal has received substantial attention as a risk factor for internalizing disorders (see Coplan et al, 2004; Coplan & Armer, 2007; Rubin et al, 2009 for reviews). Widely recognized as a heterogeneous, multifaceted construct (Gazelle & Rubin, 2010; Spangler & Gazelle, 2009; see Coplan, 2000, and Rubin, Burgess, & Coplan, 2002, for reviews), childhood social withdrawal, broadly defined, refers to a failure to engage in social interaction or play with other children (see review by Coplan et al, 2004).…”
mentioning
confidence: 99%